Chapter 5 – "Parkinson's disease – A role of non-enzymatic posttranslational modifications in disease onset and progression?". (August 2022) - Schmidt, Sebastian; Vogt Weisenhorn, Daniela M.; Wurst, Wolfgang
Abstract: Parkinson's disease (PD) is a still incurable neurodegenerative disorder with a highly complex etiology. While about 10% of cases are associated with single-gene mutations, the majority of PD is thought to originate from a combination of factors such as environmental impact, lifestyle and aging. Even though investigations into the genetically caused cases have uncovered major pathomechanisms of the disease there still exists a wide gap concerning the molecular impact of the other risk factors. All of them are known to have a major impact on the oxidative burden of the cell and thus strongly influence the non-enzymatic posttranslational modifications (nePTMs) of proteins. These modifications are by now known to dramatically alter the stability of proteins, their interactomes, and also their functions. However, the knowledge of nePTMs and their possible causative role in the pathoetiology of PD is just starting to emerge again guided by research on PD-associated genes. In this short review, we will thus concentrate on known nePTMs of two PD-associated genes, SCNA and DJ-1, and discuss their role in the pathoetiology of PD. In the future, it will, however, be essential to unravel the complete "environmental proteome" to understand the impact of nePTMs on PD etiology. This might open up new pathways urgently needed to develop new diagnostic and therapeutic tools for this still incurable disease.